ORGANIC AND MINERAL FERTILIZATION OF OIL PALM AT THE NURSERY STAGE - Kone B.; Yte W. A.; Sekou D.; Konan J. N.; Koutou A.; Konan K. E.; Zouzou M. (European Scientific Journal, ESJ, 2014)
A series of three tests of organic and mineral fertilization application was carried out (2005 to 2007) at the industrial nursery of the CNRA research Station La Mé (5°26' N, 3°50' E, 23), in South-eastern Côte d'Ivoire. The first test was set up in completely randomized blocks and had only one factor consisting of four doses (0, 8, 20 and 35% by weight of the soil substrate) of cow dung (CD) incorporated in forest soil. The variables observed showed a positive trend of the effects according to increasing doses of CD. The second set up was set up with two factors completely randomized, according to a system composed of NPKMg (0, 62, 93 and 186 g/plant) and the CD (0, 25, 50 and 75%). In order to better target the optimum, the third test was set up with new doses of CD (0, 25, 30, 35 and 40%). The results observed with the parameters in the second set up showed a high variability of the effects of fertilizers combined to CD which was either in favour of low doses or in favour of high doses applied. Some high doses (50 and 75% CD) have sometimes induced negative effects on growth variables. The third test was characterized by constant differences between CD doses. This third set up enabled, by the best effects on the all of observed variables, the choice of dose 30% CD, as the optimum, without use of mineral fertilizers.